Tetrazolium Reduction as a Measure of Metabolic Activity for Glass-Adherent Mycoplasma pneumoniae - DiVecchia, Loretta (1973)
The reduction of tetrazolium was used to assay the metabolic capability of developing Mycoplasma pneumoniae cultures on glass. Generally, the amount of tetrazolium reduced correlates with the amount of growth as measured by protein. Until a culture enters the late phase of the growth cycle, the drop in pH of culture medium provides similar information. In this last stage of growth, protein appears to be leveling. The pH continues to fall, but tetrazolium reducing activity decreases. Thus, considering the entire M. pneumoniae growth cycle, formazan production is a more reliable measure of metabolic capability of the organisms than either protein or pH. The reduction of tetrazolium provides a quantitative means of assessing enzymatic activities of glass-adherent M. pneumoniae.